RECONSTRUCTION OF THE RECIDIVIST GUIDANCE SYSTEM UNDER THE NEW PENAL CODE : IMPLEMENTATION OF SUPERVISORY PUNISHMENT AND SOCIAL WORK PUNISHMENT IN CORRECTIONAL INSTITUTIONS - Jasmalinda; Fauzia Zainin (Journal of Social and Economics Research, 2026)
The enactment of Law Number 1 of 2023 on the Indonesian Penal Code, effective from 2 January 2026, marks a paradigmatic shift in the national sentencing system from a single-track system oriented toward imprisonment to a double-track system that accommodates alternative punishments and measures, including supervisory punishment (Articles 65, 75, and 76) and social work punishment (Articles 65 and 85). At the same time, the new Penal Code retains and even broadens the scope of recidivism through a general recidivism regime (algemene recidive) under Article 23 in conjunction with Article 58. This study examines, from a legal-doctrinal perspective, how supervisory punishment and social work punishment may be reconstructed as instruments for the correctional treatment of recidivists, and proposes a policy framework that balances social reintegration with community protection. The study employs a normative-juridical method using statutory and conceptual approaches, analyzed prescriptively and qualitatively based on primary, secondary, and tertiary legal materials. Preliminary findings indicate that the new Penal Code does not yet explicitly regulate selective criteria for imposing supervisory or social work punishment on recidivists, necessitating harmonization between the Penal Code, Law Number 22 of 2022 on Corrections, and their implementing regulations, along with institutional strengthening of the Correctional Center (Bapas) as supervisor and community guide.